2018
DOI: 10.3341/kjo.2017.0057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reading Speed after Bilateral Bifocal and Trifocal Intraocular Lens Implantation

Abstract: PurposeTo evaluate and compare visual acuity and reading speed for Korean language between a diffractive bifocal and trifocal intraocular lens (IOL) of the same material and haptic design.MethodsWe reviewed the medical records of the patients who had undergone bilateral cataract surgery with bifocal IOLs (AT LISA 801) on the both eyes (bifocal group) and trifocal IOLs (AT LISA tri 839 MP, trifocal group). The main outcome measures were the uncorrected distance, intermediate, and near visual acuity (uncorrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Good near visual acuity does not always indicate good functional near vision, which is necessary for reading books or newspapers. Therefore, recent studies have used a reading speed test, which reflects functional near vision, to determine the clinical outcome of multifocal IOLs 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Good near visual acuity does not always indicate good functional near vision, which is necessary for reading books or newspapers. Therefore, recent studies have used a reading speed test, which reflects functional near vision, to determine the clinical outcome of multifocal IOLs 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…One study that compared the reading speeds of patients with a bifocal IOL (AT Lisa,) to those of patients with Trifocal IOL(AT Lisa Tri)found no significant difference between the two groups 14 . Another study reported no difference in reading speed between patients with a bifocal IOL (ReSTOR) and those with the Symfony IOL 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the AT LISA subgroup, UIVA and DCIVA were significantly better in the trifocal IOLs (AT LISA tri 839M). Many researches have confirmed better intermediate visual performance of AT LISA tri 839M trifocal IOLs than the AT LISA bifocal IOLS in both clinical study and the optical bench[22][23][24][25], which prove that the AT LISA tri 839M can provide a third effective focus. Additionally, no difference was found for the UIVA and DCIVA between the bifocal (Re STOR bifocal IOLs) and the trifocal IOLs(Fine Vision trifocal IOLs) in another subgroup.…”
mentioning
confidence: 99%